(untitled) (Al-Academy, 2024)
The dynamics of the actor’s movement in the theatrical performance are one of the most important elements that contribute to conveying the artistic message and theatrical text to the audience in an influential and effective manner. Movement is not just physical movements on the stage, but rather an expressive language that carries within it many feelings and ideas, and contributes to building characters and developing the dramatic plot. The research is summarized in four chapters. The first chapter included the research problem. The researcher formulated his problem question as follows: What are the most effective methods and techniques for the dynamics of the actor’s movement in Iraqi theater performances? Then the importance of the research and the need for it. The goal of the research was to identify the dynamics of the actor’s movement in Iraqi theater performances, then the limits of the research, followed by defining the research terms. The theoretical framework, which is the second chapter, came in two sections. The first reviewed the development of the theatrical actor’s movement from a historical perspective. As for the second section, the researcher focused on the dynamics of the actor’s movement in global theatrical theories, followed by what the theoretical framework resulted in. As for the third chapter, which is the procedural chapter, the researcher explained the research community, its method, sample, tool, and sample analysis. This is followed by the fourth and final chapter, which included the results, conclusions, recommendations, and suggestions, then a list of sources and references